The Development of AI in Medicine and the Research Environment of the SPHINX Project at the Start of the 1980s - Fieschi, M. (Yearbook of Medical Informatics, 2012)
To review the history of AI in Medicine in the 1980’s, placing the SPHINX system in the context of other research in this field.Summarize the main systems for AI in medicine devel- oped in the 1970-1980 decade and their relationship to the de- velopment of clinical decision-making and consultation systems.The approaches taken by AI in medicine research groups is compared and contrasted to those of others using statistical and logical methods for representing clinical inferences, and the different AI approaches are summarized, and related to the archi- tecture and systems implementation of SPHINX.The SPHINX system combined a number of advanced representational and inference choices from AI in designing a de- cision-support system for clinical consultation in the 1980s. The context within which the system was developed is outlined and related to the historical evolution of AI in medicine during that decade.
Keywords: Artificial Intelligence(AI) in medicine; history; SPHINX Project; frame representation; production-rules